2020
DOI: 10.9734/jammr/2020/v32i230365
|View full text |Cite
|
Sign up to set email alerts
|

Association of Clinicopathological Features with Lymph Node Metastasis: A Cross Sectional Study of Oral Squamous Cell Carcinoma Patients

Abstract: Aims:The aim of this study is to determine association between lymph node metastasis and various clinico-pathological parameters in order to predict their future prognosis of cancer patients. Study Design: Cross sectional study design. Place and Duration of Study: Ziauddin Hospital, North Nazimabad campus, Karachi. Methodology: November 2018 to September 2019. Results: The present study enrolled 140 OSCC patients visiting Ziauddin University of which 30 (21.4%) were females and 110 (78.6%) were male patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Our results are comparable with studies by Yokokawa et al 16 and Capote-Moreno et al 21 reported mean age of 59.1 and 65.3 years, respectively. However, in some studies, younger age was observed 45.6, 46.99, and 47.6 years by Mahmood et al, 22 Abidi et al, 23 and Anwar et al 4 This difference in age is probably due to risk factor exposure at an early age in certain regions of the world.…”
Section: Discussionmentioning
confidence: 94%
“…Our results are comparable with studies by Yokokawa et al 16 and Capote-Moreno et al 21 reported mean age of 59.1 and 65.3 years, respectively. However, in some studies, younger age was observed 45.6, 46.99, and 47.6 years by Mahmood et al, 22 Abidi et al, 23 and Anwar et al 4 This difference in age is probably due to risk factor exposure at an early age in certain regions of the world.…”
Section: Discussionmentioning
confidence: 94%